2021
DOI: 10.1038/s41598-021-85049-0
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin reuptake inhibitor Fluoxetine inhibits SARS-CoV-2 in human lung tissue

Abstract: To circumvent time-consuming clinical trials, testing whether existing drugs are effective inhibitors of SARS-CoV-2, has led to the discovery of Remdesivir. We decided to follow this path and screened approved medications "off-label" against SARS-CoV-2. Fluoxetine inhibited SARS-CoV-2 at a concentration of 0.8 µg/ml significantly in these screenings, and the EC50 was determined with 387 ng/ml. Furthermore, Fluoxetine reduced viral infectivity in precision-cut human lung slices showing its activity in relevant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
118
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 9 publications
9
118
0
Order By: Relevance
“…On the other hand, we have found that the non-FIASMA compounds venlafaxine and reboxetine (Kornhuber et al, 2011) also demonstrate antiviral activity. Moreover, citalopram, one of the compounds that was found to reduce the ASM activity, albeit at weaker level (Kornhuber et al, 2008), remains ineffective against native SARS-CoV-2 virus as shown by the present study and by others (Zimniak et al, 2021). Therefore, inhibition of ASM by these drugs can only partially explain the role of psychoactive drugs for the reduction of SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…On the other hand, we have found that the non-FIASMA compounds venlafaxine and reboxetine (Kornhuber et al, 2011) also demonstrate antiviral activity. Moreover, citalopram, one of the compounds that was found to reduce the ASM activity, albeit at weaker level (Kornhuber et al, 2008), remains ineffective against native SARS-CoV-2 virus as shown by the present study and by others (Zimniak et al, 2021). Therefore, inhibition of ASM by these drugs can only partially explain the role of psychoactive drugs for the reduction of SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 47%
“…Recently, a number of studies presented evidence supporting the effects of antidepressant drugs and related psychoactive drugs as antiviral compounds against SARS-CoV-2 (Carpinteiro et al, 2020;Drayman et al, 2020;Hoertel et al, 2021;Lenze et al, 2020;Marion Plaze et al, 2020;Schloer et al, 2020;Yang et al, 2020;Zimniak et al, 2021). One of these studies addressing SSRIs for their antiviral activity did not show any effect of escitalopram and paroxetine, while fluoxetine was successful with inducing antiviral activity after 3 days of treatment (Zimniak et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the view that the ASM/ceramide system is an important common target for the action of antidepressants in COVID-19. Moreover, fluoxetine can inhibit the replication of SARS-CoV-2 (Figure 3), suggesting that this drug may have a dual function, preventing cell uptake, and viral replication (Zimniak et al, 2021).…”
Section: Antidepressant Drugs and Covid-19mentioning
confidence: 99%
“…Although relatively rapid COVID-19 vaccine development has been generally considered a success, vaccine availability is currently limited by the logistical difficulties pertaining to production, storage and distribution 1 ; furthermore, periodic emergence of novel strains of the SARS-CoV-2 virus fuels recurring concerns about vaccine efficacy and future-proofing 2 . Therefore, repurposing of cheap, readily available and safe drugs against COVID-19 remains a major healthcare priority.One promising group of candidate drugs is antidepressants, which have been linked to protection against severe COVID-19 in several post-hoc clinical studies 3 , and may block SARS-CoV-2 infection and replication in cell models [4][5][6][7] . Foremost amongst these is a generic selective serotonin reuptake inhibitor (SSRI) fluvoxamine, that has been shown to protect against severe COVID-19 in a Phase 2 trial 8 as well as a real-world study 9 and is currently undergoing a Phase 3 study 10 .…”
mentioning
confidence: 99%
“…Only the drugs from the previously published list of candidates 14 were included in this work, with most of the focus being on fluvoxamine due to its clinical potential. However, emerging laboratory and clinical evidence hints at the possible therapeutic potential of other antidepressants [3][4][5]7,12 . Diversion of SARS-CoV-2 away from its productive infectious route could imply that antidepressants may not only protect against severe COVID-19, but prevent SARS-CoV-2 infection in the first place.…”
mentioning
confidence: 99%